Upaya Pencegahan dan Penanganan Awal Low Back Pain Pada Supir Taksi Bula–Ambon Kabupaten Seram Bagian Timur - Lating , Zulfikar; Dusra, Epi; Dusra, Ety (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Taxi drivers are a profession at risk of experiencing Low Back Pain (LBP). The prevalence of LBP is estimated to affect 568 million people worldwide, making it a leading cause of disability in 160 countries, with numbers expected to continue rising each year. The static position maintained for long durations while driving leads to muscle tension, exacerbating the condition. Muscle spasms occur due to reduced oxygen supply in the blood flow to the muscles. If LBP persists for a long time and recurs, it can lead to more severe pain and impact the productivity of drivers. Additionally, it can lead to other health issues such as diabetes, cardiovascular diseases, inflammation, and obesity if not balanced with adequate physical activity. Objectives: The goal is to enhance the safety, well-being, and quality of taxi drivers while developing more effective prevention strategies.Problem Statement: How can Low Back Pain (LBP) prevention efforts be implemented for taxi drivers in Bula – Ambon, not only assessing their knowledge of prevention methods but also examining their efforts in seeking treatment? Therefore, this research is expected to provide significant contributions to this area. Methodology: This study is a descriptive quantitative research aimed at illustrating the prevention and management efforts for low back pain among drivers. In this research, 56 drivers were selected as the sample, and the results were analyzed using descriptive analysis methods. Research Results: The findings indicate that 87.5% of respondents have engaged in preventive measures for Low Back Pain. Furthermore, 47 individuals (88.7%) undertook intensive actions to alleviate their pain complaints, such as increasing their intake of cold water, receiving massages for painful backs, and applying cold compresses to sore areas. However, only 18.9% sought consultation with healthcare services when experiencing back pain.